Integrating College Student Veterans on Campus through Peer Mentorship Programs - James Pease (University of Minnesota Libraries Publishing, 2021)
In 2020, approximately 2 million veterans attended colleges and universities in the U.S.  College student veterans face unique challenges integrating into campus environments and completing their degrees.  Research has shown that these students take longer to complete their degrees and have difficulty integrating into campus environments and connecting to traditional students, who are often in different developmental stages and life circumstances.  Colleges and universities across the United States vary widely in terms of resources for student veterans, with just over half offering programs for veterans.  Schools that have peer mentorship programs to enhance integration and persist in education have been shown to be successful.  In order to grow the existence of peer mentorship programs, colleges and universities should consider replicating existing models that have proven successful.  Campus stakeholders from students to administration are critical to the implementation of college student veteran peer mentorship programs. Social Work is uniquely positioned to play a key role for these programs. Social Workers can offer advocacy, clinical work, education, and scholarship to aid in the implementation of peer mentorship programs and integration of college student veterans on campus.